2015
DOI: 10.1213/ane.0000000000000576
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Incident Postoperative Delirium on Survival of Elderly Patients After Surgery for Hip Fracture Repair

Abstract: Background The impact of delirium on survival of elderly patients remains undetermined with conflicting results from clinical studies and meta-analysis. In this study we assessed the relationship between long-term mortality and incident postoperative delirium in elderly patients undergoing hip fracture repair. Methods Patients ≥ 65 years old who were not delirious before undergoing hip fracture repair were included in a database maintained prospectively from March 1999 until July 2009. All participating pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
26
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(33 citation statements)
references
References 47 publications
5
26
2
Order By: Relevance
“…Large case series report a 5.1% 30-day mortality 18 and 25% 1 yr mortality, 19 with a mean survival of 3.75 yr (95% CI, 3.13e4.54). 20 The 14% 1-yr mortality in the current study is comparable with other prospective hip fracture series, 21 but lower than the smaller randomised trial conducted by members of the same research team as the STRIDE study. 8 Exclusion criteria (severe dementia and medications which prevent the safe administration of spinal anaesthesia) were similar between these studies.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…Large case series report a 5.1% 30-day mortality 18 and 25% 1 yr mortality, 19 with a mean survival of 3.75 yr (95% CI, 3.13e4.54). 20 The 14% 1-yr mortality in the current study is comparable with other prospective hip fracture series, 21 but lower than the smaller randomised trial conducted by members of the same research team as the STRIDE study. 8 Exclusion criteria (severe dementia and medications which prevent the safe administration of spinal anaesthesia) were similar between these studies.…”
Section: Discussionsupporting
confidence: 71%
“…Similarly, previous studies have found that, when accounting for confounders, incident delirium was not an independent risk factor for intermediate-term mortality. 20,27 However, several deliriumassociated characteristics do appear to be associated with mortality. 28 Specific to surgical patients, trend-level associations between delirium severity and 6 month mortality after hip fracture repair 29 have been reported, but STRIDE is the first study to demonstrate statistically significant relationships between POD severity and 1 yr mortality.…”
Section: Discussionmentioning
confidence: 99%
“…As described previously, Cox regression analysis of all survival data from this current cohort yielded a mean 4.1 years of follow up per patient. Neither baseline cognitive impairment nor delirium survived as significant predictors of mortality in multivariate analysis (34). Similarly, when considering only one-year survival, neither probable dementia nor delirium alone was independently associated with increased mortality.…”
Section: Discussionmentioning
confidence: 99%
“…In elderly patients with hip fracture followed up for as long as 13.6 years, univariate analysis demonstrated a strong association between POD and survival, but a multivariate analysis identified only age at the time of surgery, illness severity, and duration of ICU stay after surgery as factors contributing to mortality [4]. As much as prophylaxis and treatment of POD definitely make sense from a cost and even more so from an ethical perspective, it is therefore questionable whether it will improve long-term outcome, and POD is just a marker of the fragile patient.…”
Section: Introductionmentioning
confidence: 93%